Professional organization as state agencies under the Act on Liability for Wrongful Act of Official B.E 2539 - Chaiyasit, Bhornchanok (Journal of Multidisciplinary Academic Research and Development (JMARD), 2025)
A core piece of legislation concerning the liability for wrongful acts committed by state agencies and officials is the Act on Liability for Wrongful Acts of Officials, B.E. 2539, which is intended to apply exclusively to state agencies and their officials. However, the Act allows for the designation of additional entities as state agencies through a Royal Decree. Over time, several such decrees have been issued, extending the definition of a “state agency” under the Act to include various professional organizations, such as the Medical Council, the Dental Council, the Nursing and Midwifery Council, the Council of Engineers, and the Physical Therapy Council. The legislative intent behind the Act is to impose liability on individual officials only when wrongful acts are committed with intent or gross negligence, and to ensure that liability is assigned fairly and individually, thereby protecting public officials from undue personal liability. In the Thai legal system, professional organizations are established by statute and possess legal personality. Although classified as private entities, they are vested with certain administrative powers. The inclusion of professional organizations under the scope of the Act on Liability for Wrongful Acts of Officials, B.E. 2539 raises critical questions regarding the legislative intent and the coherence of such inclusion with the overall legal framework. A close examination of the Act’s purpose and provisions suggests that it was originally designed to apply strictly to bona fide state agencies. Professional organizations, however, have a distinct legal status, differing fundamentally from that of conventional state agencies, as they are private bodies entrusted with specific administrative functions. This article aims to highlight the legal and conceptual challenges that arise from classifying professional organizations as state agencies under the Act. The analysis focuses on the rationale, necessity, and appropriateness of such classification, as well as the legal consequences that follow. It also compares the scope of legal liability imposed on professional organizations with that of other designated state agencies. The article concludes by proposing legal reforms to clearly distinguish between state agencies and professional organizations, ensuring alignment with the Act’s legislative intent and the actual legal status of professional organizations. Such reforms are essential to guarantee that both professionals and the general public are appropriately protected under the rule of law, as enshrined in the Constitution.